Modeling of Safety Training, Behaviour and Performance in Selected Oil and Gas Companies: A Case Study of the Niger Delta - , Caleb O. Onofeghara; , Ify L. Nwaogazie; , John N. Ugbebor (Archives of Current Research International, 2024)
The aim of this study is to model the safety training, safety behavior and safety performance in selected oil and gas companies in Niger delta. Safety training was segregated into teaching and practical safety trainings. Safety behavior was captured using safety compliance and safety participation while safety performance is taken as accident occurrence. The study adopted inferential research design. Multi-stage sampling technique was used to sample five companies from the study area while Taro Yamane sample size formula was used to estimate 400 samples from the study population. Structured questionnaire, designed based on 5-point Likert scale, was used for data collection; Pearson correlation, regression and t-test were used for the analyses. The Pearson coefficient of the correlation analysis results revealed that the relationship between Teaching-based Safety Training and Practical-based Safety Training was the strongest (PC = 0.818), followed by the relationship with safety compliance (PC = 0.305) and lagging safety performance (PC = 0.174) while safety participation has the weakest correlation with teaching-based safety training (PC= 0.003). It was concluded that safety training has significant impact on safety behavior and safety performance. The t-test established that there is no significant difference between teaching-based and practical-based safety trainings in the sampled oil and gas firms in Niger-Delta. Teaching-based safety training has positive but insignificant impact on reduction of accident occurrence while practical-based safety training has positive and significant impact on reduction of accident occurrence. It is recommended that management of oil and gas firms should utilize complete safety training package in order to enhance both safety behavior and safety performance of their workers.